Naphthofuroquinone derivatives show strong antimycobacterial activities against drug-resistant Mycobacteria. (2nd November 2017) - Jang, Woong Sik; Choi, Young-Sang; Kim, Sukyung; Jyoti, Md. Anirban; Seo, Hoonhee; Han, Juhye; Kim, Yong-Sik; Lyu, Jiwon; Nam, Kung-Woo; Lee, Byung-Eui; Lee, Kee-In; Song, Ho-Yeon
Abstract : Tuberculosis, one of the world's major health problems, has become more serious due to the emergence of multi-drug resistant (MDR) and extensively drug-resistant (XDR) Mycobacterium tuberculosis (MTB). In this study, we performed three anti-MTB assays to evaluate the anti-mycobacterial activity of naphthofuroquinone derivatives against drug-resistant MTB. Among them, methyl 5-[2-(dimethylamino)ethoxy]-7, 12-dioxo-7, 12-dihydrodinaphtho[1, 2-b:2′, 3′-d]furan-6-carboxylate (DFC2) exhibited strong anti-mycobacterial activity against MTB H37Ra, H37Rv and four drug-resistant MTB strains . The MIC of DFC2 ranged from 0.19–0.39 μg/ml to 0.78–1.56 μg/ml against all tested MTB strains. Moreover, DFC2 showed low cytotoxicity against fibroblast cells (L929) at concentrations 10–40-fold higher than their MICs. The IC50 value of DFC2 against L929 cells was 15.218 μg/ml. In addition, DFC2 reduced the number of intracellular M. tuberculosis in macrophages in a dose-dependent manner. Taken together, our results indicate DFC2 to be promising new candidate agents for the treatment of tuberculosis.